DIGITAL ETHIC IN ISLAM:: The Qur’anic Protype of Social Media Usage - Daimah, Daimah; Mutala’liah, Fikri Lu’lu’ul; Huda, Nurul (Jurnal Al I'jaz, 2024)
Freedom of social media as an impact of technology that is increasingly advanced and developed backfires on oneself. This freedom is misused with various forms of criminality such as fraud, cyberbullying, spreading hoax news and so on. The Qur’an as a guideline for all time, provides a perspective on the essence of social media and also implements the values of the Qur’an in addressing the digitalization of social media. The method of analysis in this research uses a qualitative approach with text studies. Data is collected from Quranic interpretations as the main instrument and supporting instruments such as scientific journal articles. The results of the findings of this study are social media as a form of interaction or social relations in a society. The implementation of Quranic values as a form of ethics is done by being careful and observant (tabayyun), using social media for good, honesty, and always developing.